Chlorella vulgaris and Chlorella pyrenoidosa live cells appear to be promising sustainable biofertilizer to grow rice, lettuce, cucumber and eggplant in the UAE soils. - Maryam Osman and T.V. Rajya Lakshmi, AreegAbd Elhafiz, AfnanAbd Elhafiz Suruchika S. Gaur, Noor Hamdany (Recent Research in Science and Technology, 2015)
The culture conditions of Chlorella vulgaris and Chlorella pyrenoidosaunder laboratory and field conditions have been standardized.Chlorella pyrenoidosa could survive under field conditions at 40Âº C in 1L cultures bottles, while C. vulgaris could not survive at this temperature. When the salt tolerance of the two species was tested against three levels of salt, C. vulgaris could survive in 1.0% NaCl with density of 87 X 104/ml cells while C. pyrenoidosa did not survive at this level of salt.Â  The total chlorophyll content (chlorophyll a and chlorophyll b) of C. pyrenoidosa is higher (1780mg/g fresh weight) than that of C. vulgaris(12360 mg/ g fresh weight) for the same mass of cells. When chlorophyll rich, salt tolerant C. pyrenoidosa live cells (11.8x104/ml) were used as biofertilizer, rice seedlings had enhanced root system, cucumber seeds had quicker germination, 1 month old seedlingshad green leaves with 2 times higher chlorophyll content than the respective control seedlings. Enrichment of salt affected soils with these green algae Chlorella vulgaris and Chlorella pyrenoidosa may be a possible option to grow these cropsin UAE.